Teaching Speaking Skills Communicatively to Promote Education 4.0: Review - Mohammad Umar Fakhrudin; Lukita, Chandra (Journal of Literature Language and Academic Studies, 2023)
Education 4.0 is a new notion in the educational field which contributes to the development technology to support teaching and learning process. Referring to its trend, many English teachers employ different approaches and methods to make teaching and learning process successfully delivered to students, especially in teaching speaking, as what is demanded in education 4.0. The approaches which is effective and frequently used is Communicative Language Teaching Approach emphasizing on its principles. Communicative Language Teaching is an approach which mainly focuses on improving the communicative competence in order to develop good communication and the use of effective language. This qualitative research is intended to discuss how to teach speaking communicatively by implementing the principles of CLT to promote Education 4.0. The writer found that by applying five principles of CLT in the form of role-play activity could effectively promote Education 4.0. Keywords: Education 4.0; Communicative Approach; the Principles of Communicative Methodology; Speaking